Anthropogenically Driven Changes to Shallow Groundwater in Southeastern Wisconsin and Its Effects on the Aquifer Microbial Communities - (:unkn) unknown (My University, 2019)
This study investigates if, and to what extent, the microbial community present in the shallow groundwater of southeastern Wisconsin is affected by the influx of treated municipal wastewater effluent. The primary study area consisted of three wells located in the shallow sand and gravel aquifer along the upper Fox River in Waukesha, Wisconsin. One well is located roughly 1500 feet from the river and pumps pristine groundwater. Two riverbank inducement wells are located within 200 feet of the river and pump a mixture of groundwater and river water that contains effluent from three upstream wastewater treatment plants. Water from all three wells was analyzed for geochemical composition (major ions, nutrients, dissolved gases and dissolved organic carbon) and microbial community composition (16S rRNA gene composition, 16S rRNA activity and metagenomic sequencing). Geochemical and microbial community data were combined to identify thermodynamically feasible metabolic pathways capable of being carried out by the microbial consortia. Geochemical results show the riverbank inducement wells differ from the pristine well in thermodynamic capabilities. Microbial results show differences in the microbial consortia present in the pristine well and the riverbank inducement wells. Microbial community taxa identified with known subsurface microorganisms, recently discovered microorganisms from the CPR and DPANN superphyla, and unclassified unknown organisms.